Serological Activity of Lipids of a T strain of Mycoplasma - Romano, Nino (1974)
Complement-fixing activity of a T strain of Mycoplasma was found to be associated with its lipid components. Heat stability and lability of periodate and β-glucosidase treatments led to the conclusion that complement-fixing, active lipids had carboydrate determinants. Periodate treatment of chromatographic fractions of a chloroform-methanol extract showed that only antigens contained in the acetone fraction were periodate labile. Lipids also appeared to be involved in the passive hemagglutination, since the lipid fraction active in complement fixation also combined and blocked the action of antibodies which agglutinated sensitized erythrocytes with strain P108.